Corrosion and corrosion control : an introduction to corrosion science and engineering. - Revie, R. Winston (Robert Winston), 1944-; Uhlig, Herbert Henry, 1907-1993 (Hoboken : Wiley, 2008)
This Fourth Edition presents an updated overview of the essential aspects of corrosion science and engineering that underpin the tools and technologies used for managing corrosion, enhancing reliability, and preventing failures. Although the basic organization of the book remains unchanged from the previous edition, this new update includes: An introduction to new topics, including the element of risk management in corrosion engineering and new advanced alloys for controlling corrosion Expanded discussions on electrochemical polarization, predicting corrosion using thermodynamics, steel reinforcements in concrete, and applications of corrosion control technologies in automotive, nuclear, and other industries A stronger emphasis on environmental concerns and regulations in the context of their impact on corrosion engineering A discussion of the challenge of reliability in nuclear reactors; stainless steels; the concept of critical pitting temperature; and information on critical pitting potential (CPP) Complemented with numerous examples to help illustrate important points, Corrosion and Corrosion Control, Fourth Edition enables readers to fully understand corrosion and its control and, in turn, help reduce massive economic and environmental loss. It is a must-read for advanced undergraduates and graduate students in engineering and materials science courses, as well as for engineers, technologists, researchers, and other professionals who need information on this timely topic.